Analisis Kemampuan Komunikasi Matematis Ditinjau dari Gaya Belajar Siswa pada Materi Persamaan Garis Lurus - Andria, Adrila; Hutapea, Nahor Murani; Suanto, Elfis (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2024)
Communication skills include the ability to express the understanding that has been obtained from learning by using mathematical language such as numbers, symbols, notations or graphs. Low category communication skills can be influenced by one of them by learning style. The purpose of this research is to analyze and describe the mathematical communication skills of students on straight line equation material when viewed from learning styles so that it can be known how the mathematical communication skills of students with visual, auditorial and kinesthetic learning styles. The method used in this research is descriptive qualitative. The research was conducted at SMPN 48 Pekanbaru with the research subjects of class VIII in the 2023/2024 school year. The data collection techniques used were tests and interviews. Tests to obtain data on students' mathematical communication skills and interviews to confirm students' answers. The results showed that visual learning style subjects obtained higher mathematical communication skills than auditorial and kinesthetic learning styles because they almost achieved all indicators of mathematical communication skills.